Extending Technology Acceptance Model with Scientific Epistemological and Science Teaching Efficacy Beliefs: A Study with Preservice Teachers - Tezcan Kartal; Ibrahim Serdar Kiziltepe; Busra Kartal (Journal of Education in Science, Environment and Health)
The technology acceptance model (TAM) is a widely used framework to investigate factors influencing technology use in education. TAM refers to a person’s technology-related attitudes and beliefs influencing intention to use and actual use of technology and seeks predictors of behaviors whether to accept or reject using technology. There are various external variables extended to TAM to increase the predictivity of the model and the generalizability of findings. However, what is not yet clear is the impact of teacher-related variables such as teaching efficacy and epistemological beliefs on teachers’ technology acceptance and behavioral intention. This study examined 710 preservice teachers’ technology acceptance using an extended-TAM with scientific epistemological and science teaching efficacy beliefs. Data were collected through a self-reported measurement tool. Structural equation modeling was used to analyze data. Results revealed that the research model explained 59% of the variance in behavioral intention, and perceived usefulness is the most prominent determinant of behavioral intention. The subdimension of scientific epistemological beliefs, justification, is the strongest determinant in influencing TAM constructs among the external variables (epistemological and science teaching efficacy beliefs). Science teaching efficacy beliefs had small effects on technology acceptance constructs. Recommendations were made based on the findings